Percutaneous Peripheral Nerve Stimulation for Pain Reduction and Improvements in Functional Outcomes in Chronic Low Back Pain. (21st March 2019) - Cohen, Steven; Gilmore, Christopher; Kapural, Leonardo; Hanling, Steven; Plunkett, Anthony; McGee, Meredith; Boggs, Joseph
Abstract: Chronic low back pain represents one of the most common sources of disability and a significant healthcare burden for the U.S. military. Present treatments for chronic back pain are often ineffective, poorly tolerated, invasive, destructive, and/or associated with complications and lead to the progression to invasive surgical procedures. There have been multiple calls for the development of a minimally invasive system that is effective without the risks or complications of existing surgical therapies, which could prevent the need for surgery and the recurrence of pain. The goal of this study was to evaluate a novel, minimally invasive approach using a percutaneous peripheral nerve stimulation (PNS) system designed to provide pain relief without surgery, to reduce complications, and provide a less-invasive treatment option. In nine subjects, percutaneous PNS improved participants' function, as evidenced by clinically and statistically significant reductions in pain, disability, and pain interference. Subjects also experienced reductions in opioid and non-opioid analgesic medication usage and reported improvements in quality of life with treatment. There were no serious or unanticipated adverse events. These results demonstrate the potential of percutaneous PNS as a non-surgical therapy to treat chronic back pain without opioids.